RESEARCH OF ADSORPTION AFLATOXINS BY TECHNICAL LIGNIN (World Science, 2021)
Aflatoxins represent aggressive group of mycotoxins. They are really toxic, carcinogenic and dangerous for human health. There are mechanical, physical and chemical methods for their detoxification. Aflatoxins could be also neutralized by means of various adsorbents as well. We do some research work in the direction of aflatoxin adsorption by presence of lignin, which is quite affordable and gives an effective result.